2023
DOI: 10.1177/00369330231187655
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: The impact of sarcopenia on prognosis of patients with pancreatic cancer: A systematic review and meta-analysis

Abstract: Objective To summarize recent findings on the association of low skeletal muscle mass and muscle quality with overall survival and recurrence-free survival in patients with pancreatic cancer. Methods A systematic search was conducted using Medline (via PubMed), Embase and Scopus databases for observational studies reporting on the overall survival and recurrence-free survival. Pooled effect sizes were reported as hazards ratio along with 95% confidence intervals. Results A total of 34 studies were included. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…The remaining part of the issue has some more papers on evidence synthesis. Gan et al 2 have summarised impact of sarcopenia on the outcome of pancreatic cancer. The term ‘sarcopenia’, originates from Greek language.…”
mentioning
confidence: 99%
“…The remaining part of the issue has some more papers on evidence synthesis. Gan et al 2 have summarised impact of sarcopenia on the outcome of pancreatic cancer. The term ‘sarcopenia’, originates from Greek language.…”
mentioning
confidence: 99%
“…Meyer et al found that sarcopenia was a prognostic marker for survival in gastric cancer undergoing palliative chemotherapy (13). Additionally, Gan H et al pointed out both low skeletal muscle mass and poor muscle quality were relative with poor long term survival of patients with pancreatic cancer (14). The Computed tomography (CT) scans enable the measurement of the third lumbar spine skeletal muscle index (L3-SMI).…”
Section: Introductionmentioning
confidence: 99%
“…The range of topics of systematic reviews. [1][2][3][4][5][6][7][8] in this issue has been wide and not focusing on a particular problem, however, publications should generate awareness, some glimpse into methodology and associated discussions around evidence-based medicine.Evidence-based medicine is a combination of individual clinical knowledge and the results of clinical trials. And as a doctor, there is a great need for some strong evidence to support his diagnosis and treatment and all aspects of it.…”
mentioning
confidence: 99%
“…The range of topics of systematic reviews. [1][2][3][4][5][6][7][8] in this issue has been wide and not focusing on a particular problem, however, publications should generate awareness, some glimpse into methodology and associated discussions around evidence-based medicine.…”
mentioning
confidence: 99%